Contested psychiatric ontology and feminist critique: ‘Female Sexual Dysfunction’ and the Diagnostic and Statistical Manual - Angel, Katherine (History of the Human Sciences, 2012)
In this article I discuss the emergence of Female Sexual Dysfunction (FSD) within American psychiatry and beyond in the postwar period, setting out what I believe to be important and suggestive questions neglected in existing scholarship. Tracing the nomenclature within successive editions of the American Psychiatric Association’s Diagnostic and Statistical Manual (DSM), I consider the reification of the term ‘FSD’, and the activism and scholarship that the rise of the category has occasioned. I suggest that analysis of FSD benefits from scrutiny of a wider range of sources (especially since the popular and scientific cross-pollinate). I explore the multiplicity of FSD that emerges when one examines this wider range, but I also underscore a reinscribing of anxieties about psychogenic aetiologies. I then argue that what makes the FSD case additionally interesting, over and above other conditions with a contested status, is the historically complex relationship between psychiatry and feminism that is at work in contemporary debates. I suggest that existing literature on FSD has not yet posed some of the most important and salient questions at stake in writing about women’s sexual problems in this period, and can only do this when the relationship between ‘second-wave’ feminism, ‘post-feminism’, psychiatry and psychoanalysis becomes part of the terrain to be analysed, rather than the medium through which analysis is conducted.
Number: 4
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; europe; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Elles eurent beaucoup d'enfants– et se marièrent histoire d'une famille homoparentale - Blanc, Myriam (Bec en l'air, 2012)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; filiation; france; hétérosexisme; identités LGBTQIA2+; mariage; maternité; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

À propos des rapports sociaux de sexe. - Kergoat, Danièle (Se battre, disent-elles .., 2012)
Recueil de textes de cette figure du féminisme et pionnière de la sociologie du travail et du genre en France. Il éclaire la construction d'analyses et de concepts autour de la division sexuelle du travail, des rapports sociaux de sexe, leur intrication avec les rapports de classe et de race. L'ensemble permet de retracer le chemin intellectuel et politique de D. Kergoat.
Section: 1 vol. (354 p.) : couv. ill. en coul., tabl. ; 23 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; travail

Comment peut-on être lesbienne ? Hétéronorme et hétérosexisme des fictions télévisées françaises - Rollet, Brigitte (Entrelacs, 2012)
Cet article porte sur les constructions télévisuelles de l’homosexualité féminine depuis 1995, moment marquant une augmentation de la visibilité des gays et lesbiennes sur le petit écran. A partir de Tous les papas ne font pas pipi debout (1999) et La surprise (2007) , je repérerai les tendances dominantes des fictions montrant en prime-time sur une chaîne de service public, des modes de vie supposément alternatifs afin d'analyser comment se construit la transgression (s’il en est) de ces héroïnes différentes (ou pas ?) à la télévision française depuis la fin du siècle dernier (après le Pacs donc). Le rôle de la maternité et le statut de mère des protagonistes seront également envisagés.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; europe; france; hétérosexisme; identités LGBTQIA2+; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; série télévisée